Blast injury on harbour porpoises (Phocoena phocoena) from the Baltic Sea after explosions of deposits of World War II ammunition. (15th January 2022) - Siebert, Ursula; Stürznickel, Julian; Schaffeld, Tobias; Oheim, Ralf; Rolvien, Tim; Prenger-Berninghoff, Ellen; Wohlsein, Peter; Lakemeyer, Jan; Rohner, Simon; Aroha Schick, Luca; Gross, Stephanie; Nachtsheim, Dominik; et al.
Highlights: First study on effects of clearance of ammunition dumped in large amounts into the sea during and after World War II. Harbour porpoises highly endangered in the Baltic Seas. Severe lesions due to blast trauma found in porpoises from the Baltic Sea. Microfractures and discolation of middle ear bone due to blast trauma. Environmental effects need to be managed at international level. Abstract: Harbour porpoises are under pressure from increasing human activities. This includes the detonation of ammunition that was dumped in large amounts into the sea during and after World War II. In this context, forty-two British ground mines from World War II were cleared by means of blasting in the period from 28 to 31 August 2019 by a NATO unit in the German Exclusive Economic Zone within the marine protected area of Fehmarn Belt in the Baltic Sea, Germany. Between September and November 2019, 24 harbour porpoises were found dead in the period after those clearing events along the coastline of the federal state of Schleswig-Holstein and were investigated for direct and indirect effects of blast injury. Health evaluations were conducted including examinations of the brain, the air-filled (lungs and gastrointestinal tract) and acoustic organs (melon, acoustic fat in the lower jaw, ears and their surrounding tissues). The bone structure of the tympano-periotic complexes was examined using high-resolution peripheral quantitative computed tomography (HR-pQCT). In 8/24 harbour porpoises, microfractures of the malleus, dislocation of middle ear bones, bleeding, and haemorrhages in the melon, lower jaw and peribullar acoustic fat were detected, suggesting blast injury. In addition, one bycaught animal and another porpoise with signs of blunt force trauma also showed evidence of blast injury. The cause of death of the other 14 animals varied and remained unclear in two individuals. Due to the vulnerability and the conservation status of harbour porpoise populations in the Baltic Sea, noise mitigation measures must be improved to prevent any risk of injury. The data presented here highlight the importance of systematic investigations into the acute and chronic effects of blast and acoustic trauma in harbour porpoises, improving the understanding of underwater noise effects and herewith develop effective measures to protect the population level.